The exact worst-case convergence rate of the gradient method with fixed step lengths for L-smooth functions - Abbaszadehpeivasti, Hadi; de Klerk, Etienne; Zamani, Moslem (Optimization letters, 2022)
In this paper, we study the convergence rate of the gradient (or steepest descent) method with fixed step lengths for finding a stationary point of an L -smooth function. We establish a new convergence rate, and show that the bound may be exact in some cases, in particular when all step lengths lie in the interval (0, 1/ L ]. In addition, we derive an optimal step length with respect to the new bound.